A comparative finite element analysis of titanium, poly-ether-etherketone, and zirconia abutment on stress distribution around maxillary anterior implants - Angel Elias; R. Fathima Banu; Anand Kumar Vaidyanathan; T. V. Padmanabhan (Wolters Kluwer Medknow Publications, 2024)
Background: The aim of this study was to investigate the influence of abutment material, alveolar bone density, and occlusal forces on stress distribution around maxillary anterior implants. Materials and Methods: An in-vitro study was conducted. The maxillary anterior implant was modeled using a three-dimensional finite element model in D2 and D3 bones with three different abutment materials: titanium, zirconia, and poly-ether-ether ketone (PEEK). Von Mises stress was evaluated after the application of vertical and oblique loads of 100 N, 175 N, and 250 N. Statistical analysis was done by Friedman-Wilcoxon signed-rank test, Mann-Whitney U test, and Kruskal-Wallis test. The probability value <0.05 is considered a significant level. Results: Stress distribution around D3 bone was higher than D2 bone in all the abutment materials with greater values seen in oblique load than vertical load with insignificant difference ( P > 0.05). Statistically insignificant stress values were seen greater in PEEK than titanium or zirconia abutment ( P > 0.05). A statistically significant difference was observed between 100 N and 175 N of load ( P < 0.05). Conclusion: PEEK, zirconia, and titanium as abutment material in the anterior region showed similar properties. The stress on the bone was proportionately increased during the vertical and oblique loads suggesting the influence of mechanical load in crestal bone loss rather than the type of abutment material.